2018
DOI: 10.1177/1470785318762990
|View full text |Cite
|
Sign up to set email alerts
|

A consumer-based brand performance model for assessing brand success

Abstract: The aim of this study is to introduce a Consumer-Based Brand Performance Model (CBBPM) to measure brand success. The CBBPM consists of four critical constructsbrand equity, brand trust, brand satisfaction and brand loyaltyand is applied across different product categories and brands. In total, 881 consumers participated in the survey, and a structural equation modelling approach was employed to test the research hypotheses. The findings of the study suggest that the CBBPM is valid and reliable. Brand equity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 58 publications
3
44
0
2
Order By: Relevance
“…Past studies emphasized the role of service quality in the determination of customer satisfaction which customer encounters at the restaurant setting (dimensions: friendliness staff, courteous, quick service line, waiting time, etc. [40] as well as the consumer's behavioral intention to revisit [41]. Thus, we can extrapolate from previous findings that improved service quality results in a satisfied or contented customer [42] which leads to brand loyalty.…”
Section: Service Qualitymentioning
confidence: 56%
“…Past studies emphasized the role of service quality in the determination of customer satisfaction which customer encounters at the restaurant setting (dimensions: friendliness staff, courteous, quick service line, waiting time, etc. [40] as well as the consumer's behavioral intention to revisit [41]. Thus, we can extrapolate from previous findings that improved service quality results in a satisfied or contented customer [42] which leads to brand loyalty.…”
Section: Service Qualitymentioning
confidence: 56%
“…Molinillo, Ekinci, and Japutra [56] used brand equity as a predictor of brand satisfaction, brand trust, and brand loyalty. The authors [21] measured brands' marketing activities on social media as a general concept that includes five features (entertainment, interaction, trendiness, customization, and word of mouth).…”
Section: Smmas Impacts On Brand Equity (Brand Awareness Brand Image)mentioning
confidence: 99%
“…In a study conducted by Molinillo et al (2018), a 'Consumer-Based Brand Performance Model' (CBBPM) was introduced to measure how successful a brand is. The study determined that the factors "brand equity, brand satisfaction and brand trust are prominent variables in explaining brand loyalty" (Molinillo et al, 2018, p. 16).…”
Section: Assessing Brand Advantagementioning
confidence: 99%
“…They were asked about their choice of the brand they were familiar with when given different brands. Molinillo et al (2018) then found that consumer-based brand equity (CBBE) has a positive influence on brand satisfaction, brand trust as well as brand loyalty and, in conclusion, that increased brand equity increases success.…”
Section: Assessing Brand Advantagementioning
confidence: 99%